ANALISIS DAMPAK LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA SERTA IMPLIKASINYA PADA KINERJA GURU SD DI KECAMATAN BANDAR BARU KABUPATEN PIDIE JAYA - Kamaruddin Kamaruddin; Win Konadi; Sri Hidayati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The study was conducted on a sample of 227 SD Negeri Bandar Baru Pidie Jaya teachers, with the aim of knowing; 1) the partial effect of work environment and organizational culture on teacher job satisfaction, 2) the effect of job satisfaction on teacher performance, and 3). The influence of the work environment and organizational culture through job satisfaction has implications for teacher performance. This research is in the form of a survey using quantitative descriptive methods and associative analysis between variables using a path analysis approach. The results of the study found that; a). There is a direct and indirect influence of work environment factors on teacher job satisfaction of 85.64%, while the influence of school organizational culture factors on teacher job satisfaction is 86.08%. b). there is an effect of job satisfaction on teacher performance, which is 15.76%. c). There are direct and indirect effects of the three factors (variables) studied on performance, namely the influence of the work environment by 28.13%, the influence of teacher job satisfaction factors by 15.76% and the influence of school organizational culture factors by 35.23% on the performance of elementary school teachers. in Bandar Baru District, Pidie Jaya Regency by 64.10%.